The Evolution of Antitrust Law in USA - Lamaj, Jonida (European Scientific Journal, ESJ, 2017)
This Article analyzes the evolution of Antitrust Law (known as Competition Law in Europe) in United States of America. It is important to study the history of Antitrust Law in USA, because the roots and the origin of this important law and regulation that guarantee the economic rights and freedoms of persons and companies has started in USA, inherited from the Common Law system. This Article is composed by 4 main components, such as: Introduction of Antitrust Law, History of Sherman Act, History of Clayton Act and The enforcement of Competition Law in USA. A greater attention is given to the Sherman Antitrust Act. To better understand the Sherman Act, it is described the history path of the legalization of the act, reason why this act was implemented in USA, which were some challenges of the system at that time, how it is enforced, etc.? The same analogy is done with the Clayton Act and other amendments of Antitrust Acts. At the end of the paper it is introduced the main tools that helps to function the Antitrust law in USA, by analyzing the role of Department of Justice Antitrust Division, the Federal Trade Commission and Exemptions and Immunities.